Monolithic capillary column with an integrated electrochemical detector - Komendová, Martina; Metelka, Radovan; Urban, Jiří (Journal of chromatography. A, Including electrophoresis and other separation methods, 2017)
The carbon fiber and silver microwire were used as working and pseudoreference electrode, respectively, and inserted into the ending of capillary to prepare monolithic capillary column with an integrated electrochemical detector. Prepared capillary devices offered stable and robust results with relative standard deviations of retention, resolution, and detection signal lower than 1.5, 5.5, and 5.0%, respectively. To further increase sensitivity of developed electrochemical microdetector, multiple pulse amperometry detection mode has been used. Optimized integrated device provided reliable chromatographic separation of mixture of neurotransmitters with calibration curve for dopamine linear from 0.5 to 20.0mgL-1 and an instrumental limit of detection as low as 24pg of injected dopamine. Finally, developed capillary column was applied to successful determination of dopamine in a human urine. By using both calibration curve and standard addition method, the dopamine level was determined to be 0.74±0.03mgL-1 and 0.71±0.02mgL-1, respectively. Triplicates of dopamine analysis provided relative standard deviations lower than 2.7% for intraday analyses, while interday relative standard deviations were lower than 3.6% for five consecutive days.
Keywords: elektrody; elektrochemické techniky; Dopamine; Neurotransmitter Agents; neurotransmiterové látky; Electrodes; lidé; Humans; dopamin; Electrochemical Techniques